2021
DOI: 10.1007/s11571-021-09732-8
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor rhythm neurofeedback training relieves anxiety in healthy people

Abstract: Timely relief of anxiety in healthy people is important, but there is little research on this topic at present. Neurofeedback training allows subjects to regulate their specific brain activities autonomously and thus alter their corresponding cognitive functions. Inattention is a significant cognitive deficit in patients with anxiety. Sensorimotor rhythm (SMR) was reported to be closely related to attention. In this study, trainability, frequency specificity, and brain-behavior relationships were utilized to v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…Previous research has shown that BFB treatment can benefit disorders such as epilepsy [8], migraine [9], stroke [10], chronic insomnia [11,12], anxiety [13], attention-deficit/hyperactivity disorder [14,15], autism spectrum disorder [16], and major depression [17]. As a BFB method, neurofeedback training allows individuals to independently adjust specific brain activities, thereby changing their cognitive functions [18]. BFB is based on the idea that autonomic responses may be conditioned by instrumentation and includes biological monitors and sensors such as electromyography (EMG), EEG, electrodermal activity, skin temperature, HR, HRV, and end-tidal carbon dioxide [19].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that BFB treatment can benefit disorders such as epilepsy [8], migraine [9], stroke [10], chronic insomnia [11,12], anxiety [13], attention-deficit/hyperactivity disorder [14,15], autism spectrum disorder [16], and major depression [17]. As a BFB method, neurofeedback training allows individuals to independently adjust specific brain activities, thereby changing their cognitive functions [18]. BFB is based on the idea that autonomic responses may be conditioned by instrumentation and includes biological monitors and sensors such as electromyography (EMG), EEG, electrodermal activity, skin temperature, HR, HRV, and end-tidal carbon dioxide [19].…”
Section: Introductionmentioning
confidence: 99%
“…Previous researches have found that Biofeedback training bene ts the interventions of several disorders: such as epilepsy [9], migraine [10], stroke [11], chronic insomnia [12,13], anxiety [14], attention de cit/hyperactivity disorder (ADHD) [15,16], autism spectrum disorder [17], major depression [18]. Neurofeedback training allows individuals to independently adjust their speci c brain activity, thereby changing their corresponding cognitive function [19]. Biofeedback is based on the idea that autonomic responses may be conditioned by instrumentation, and includes biological monitors and sensors such as electromyography, electroencephalography, electrodermal activity, skin temperature, heart rate (HR) and heart rate variability (HRV), and end-tidal carbon dioxide biofeedback [20].…”
Section: Introductionmentioning
confidence: 99%